The Gagauz people in Bulgaria, Moldova and Ukraine – chosen aspects - Hatłas, Jerzy (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The Gagauz people are an interesting example of a modern micro-nation. They came into being on the Balkan Peninsula. Yet their ethnogenesis is a mystery since direct written sources are missing. There are many theories about their origin. The Gagauz are most frequently perceived as a people of the Turkic origin. Bulgarian scholars view them as Turkified Bulgarians. In the very Bulgaria there remained only very few Gagauzians. This state of affairs is caused by the fact that the majority of Gagauzians emigrated and the remaining ones underwent assimilation. Nowadays they mainly inhabit Bessarabia (in southern Moldova or the western part of the Odessa district in Ukraine). In Moldova their autonomy is recognized by the state. The Gagauzian identity looks different in those three countries. In Bulgaria Gagauzians still have a double identity. They feel both Gagauzians and Bulgarians. In Moldova and Ukraine, in turn, they consider themselves as a separate nation. As far as the Gagauzian faith is concerned, they are everywhere mainly connected with the Orthodox faith. In regard to the Gagauzian-Bulgarian antagonisms one can state that these are the echo of times gone by. These days cooperation and neighborly relations prevail. In their attitudes to Russia, Bessarabian Gagauzians are predominantly Russophiles. Nostalgia for communism and the USSR is widespread. Gagauzians in Bulgaria are not anti-Russian but their view of Russia is not solely idealistic.